Three‐year survival of transcatheter versus surgical aortic valve replacement in dialysis. Issue 4 (27th January 2022) - Ogami, Takuya; Kurlansky, Paul; Takayama, Hiroo; Ning, Yuming; Zimmermann, Eric; Zhu, Roger C.; Ali, Ziad A.; Nazif, Tamim M.; Vahl, Torsten P.; Avgerinos, Dimitrios V.; Smith, Craig R.; Leon, Martin B.; et al.
Abstract: To highlight the trends of surgical (open) aortic valve replacement (SAVR) as well as to compare the outcome between transcatheter aortic valve replacement (TAVR) and SAVR in elderly dialysis patients. TAVR has evolved as an effective alternative to surgery (SAVR) for aortic stenosis. We identified dialysis‐dependent patients who underwent SAVR or TAVR from 2000 to 2015 from the United States Renal Data System using ICD‐9 codes. We defined high‐risk surgical patients as age over 70 or older. The primary endpoint was survival at 3 years and we compared the outcome between SAVR and TAVR groups using inverse probability of treatment weighting (IPTW). A total of 4332 and 1280 dialysis patients underwent SAVR and TAVR, respectively, during the study period. Among SAVR cohort, 3312 patients underwent SAVR before June 2012 and 1020 after June 2012. In‐hospital mortality was significantly worse before 2012 (14.6% vs. 11.3% after 2012, p = 0.007) as well as estimated 3‐year mortality (69.1% vs. 60.3% after 2012, p < 0.001). After June 2012, the TAVR cohort was older and had more comorbidities including coronary artery disease and congestive heart failure compared to the SAVR cohort. After IPTW, in‐hospital mortality was significantly lower after TAVR versus SAVR (odds ratio 0.38 [95% confidence interval [CI], 0.27–0.52], p < 0.001). However, TAVR had a significantly higher risk of 3‐year mortality than SAVR (hazard ratio 1.24 [95% CI 1.1–1.39], p < 0.001). TAVR may be a reasonable and potentially preferable alternative to SAVR in the elderly dialysis population in the short‐term period.